PERILAKU MASYARAKAT DI ERA DIGITAL (STUDI DI KELURAHAN TINGKULU KECAMATAN WANEA KOTA MANADO) - PALIT, ROSALINDA; LALOMA, ALDEN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine how the behavior of the people in Tingkulu Village, WaneaDistrict, Manado City in the Digital Age. The research method used in this research is descriptive researchmethod with a qualitative approach. Data collection in this study was carried out through interviews,observation and document collection. The core problem of this research is the existence of bad attitudes insociety in using digital technology today. Based on the research results, it can be concluded that people'sbehavior in the digital era, especially in Tingkulu Village, has developed, even the Tingkulu Villagecommunity currently shows the attitude of modern society. In its use there are good and bad behaviors suchas the creation of the behavior of modern society that has a fairly good thought and understanding inutilizing digital technology, is easy to communicate, easy to get and share information, the formation ofindividualistic behavior, insinuate, spit people's badness others, venting anger, and hate speech.Keywords: Behavior, Society, Digital Age